Design of Pest Detection and Repellent Device Based on Arduino Uno using Pir (Passive Infrared Receiver) Sensor - Nur Adi Prasetyo; Muhajir Syamsu; Shevti Arbekti Arman (Journal of Computer Science Advancements, 2024)
This research aims to design and develop a technology-based pest detection and repellent device using the Arduino Uno R3 microcontroller. This tool is designed to overcome the problem of the presence of insect pests and rats on the KWT Gemas Imlan agricultural land. The developed system integrates various sensors and modules to achieve optimal performance. The PIR sensor is used to detect the movement of pests around agricultural areas, while the LDR sensor functions to measure light intensity as one of the parameters of equipment operating conditions. As an expulsion measure, this device is equipped with an NE555 module which emits high frequency sound waves to repel or force pests to leave the agricultural area. Testing is carried out in stages, starting from individual testing of each sensor to testing the entire system. The research results show that this tool can operate automatically with a fast and accurate response, so it has the potential to be an effective solution for controlling pests on agricultural land.